PERHITUNGAN CADANGAN BATUBARA TERBUKTI DENGAN MENGGUNAKAN PROGRAM MINESCAPE 4.118 PADA PIT 2 DI CV. BINTANG SURYA UTAMA KABUPATEN KUTAI KARTANEGARA PROVINSI KALIMANTAN TIMUR (Jurnal Geologi Pertambangan (JGP), 2016)
In the research location, there are three seams coal, based from the stratigraphy sequence which is, seam 3 (average thickness 0,44 meters with calories 5.456 cal/g), seam 2 (average thickness 3,07 meters with calories 5.850 cal/g) and seam 1 (average thickness 0,97 meters with calories 5.521 cal/g). Based on calorific value and quantitative condition of the coal thickness and dirty layer (SNI 2011), therefore seam coal that proper to be counted as proved coal reserve that only 2 seam coal, which is seam 2 and seam 1 with separate open pit. Seam 2 could be called pit 2 that has coal deposit 126.410,35 tons and the volume of overburden 1.168.664,09 bcm with stripping ratio 9,24 and wide of pit 60.458,37 m2. Seam 1 could be called pit 2A that has coal deposit 9.528,64 tons and the volume of overburden 97.980,89 bcm with stripping ratio 10,28 and wide of pit 15.952,39 m2. Therefore total of proved coal reserve in the research location for seam 2 and seam 1 is 135.938,99 tons and volume of overburden 1.266.644,98 bcm with stripping ratio 9,32 and overall wide of pit 76.410,76 m2. Mean while seam 3 is not feasible and will be as proved coal reserve with marginal value 4.222,99 tons. From the calculation results of proved coal reserve in this research location, we need to know there are few factors that could be affect coal deposit, such as geological condition, exploration, geotechnical, heavy equipment and also plan of hauling road in the pit.Keywords : Proved coal reserves, Stripping Ratio, Seam.